DROP SIZE AND DISPERSED PHASE HOLDUP IN A SPRAY COLUMN (Biological Sciences - PJSIR, 2022)
Drop size and dispersed phase holdup in a spray column for a reactive extraction system (zinc/di (2-ethylhexyl)phosphoric acid) has been obtained under solute transfer from continuous to dispersed and dispersed to continuousphase. A photographic method is used for the estimation of drop size and dispersed phase holdup. The experiments arecarried out in a glass spray column operated under semi-batch mode, i.e. the continuous aqueous phase is kept stagnantand the dispersed phase is not recirculated. Dispersed phase velocity through the nozzles is varied from 3.4 x 10-2 to24.5xlO-2 m/s. Nozzle diameter ranges from 0.8 x 10-3 to 3 x la-3m.